2017
DOI: 10.1038/s41598-017-08433-9
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potential biomarkers in human melanoma cells with different metastatic potential by metabolic and lipidomic profiling

Abstract: Malignant melanoma, characterized by its ability to metastasize to other organs, is responsible for 90% of skin cancer mortality. To investigate alterations in the cellular metabolome and lipidome related to melanoma metastasis, gas chromatography-mass spectrometry (GC-MS) and direct infusion-mass spectrometry (DI-MS)-based metabolic and lipidomic profiling were performed on extracts of normal human melanocyte (HEMn-LP), low metastatic melanoma (A375, G361), and highly metastatic melanoma (A2058, SK-MEL-28) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 70 publications
3
84
1
3
Order By: Relevance
“…Beyond this metabolic reprogramming, and since glucose is converted almost quantitatively to lactic acid, the TCA (tricarboxylic acid) cycle functions, regardless of oxygen presence, in the reverse direction, using glutamine as an alternative carbon source [10]. Elevated glycolysis and glutaminolysis could explain the absence of both glucose and glutamine metabolites from the two cell lines, WM115 and WM2664, but most importantly the significant increase in lactic acid (FC NMR = 3.27) and glutamic acid (FC NMR = 4.84; FC MS = 5.81), as well as in the TCA cycle intermediates fumaric acid (FC NMR = 2.01) and succinic acid (FC NMR = 4.82; FC MS = 4.04) [11], in the metastatic melanoma cell line WM2664. A rise in the (metabolite-linker) alanine content [10] from implementation of these two processes is expected, since alanine aminotransferase catalyzes the transfer of an amino group from glutamic to pyruvic acid, with alanine and oxoglutaric acid being the reaction products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond this metabolic reprogramming, and since glucose is converted almost quantitatively to lactic acid, the TCA (tricarboxylic acid) cycle functions, regardless of oxygen presence, in the reverse direction, using glutamine as an alternative carbon source [10]. Elevated glycolysis and glutaminolysis could explain the absence of both glucose and glutamine metabolites from the two cell lines, WM115 and WM2664, but most importantly the significant increase in lactic acid (FC NMR = 3.27) and glutamic acid (FC NMR = 4.84; FC MS = 5.81), as well as in the TCA cycle intermediates fumaric acid (FC NMR = 2.01) and succinic acid (FC NMR = 4.82; FC MS = 4.04) [11], in the metastatic melanoma cell line WM2664. A rise in the (metabolite-linker) alanine content [10] from implementation of these two processes is expected, since alanine aminotransferase catalyzes the transfer of an amino group from glutamic to pyruvic acid, with alanine and oxoglutaric acid being the reaction products.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolite that demonstrated the most striking difference between the two cell lines, WM115 and WM2664, was hypoxanthine, whose concentration was measured at least 14-fold (x) higher in WM2664 (FC NMR = 14.05; FC MS = 94.26), as compared to WM115 (reference) cells. Metabolic studies for gastric cancer and melanoma have described higher plasma and tissue levels, due to higher tumor-cell proliferation rates, conditions under which hypoxanthine acts as a substrate and source of nitrogen [11,47]. Hypoxanthine is formed via the Purine Biosynthesis Pathway (PBP) [48] that is characterized by the conversion of ribose 5-phosphate to inosine monophosphate (FC NMR = 1.45), which is, then, dephosphorylated to inosine, the major hypoxanthine precursor molecule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we observed that both SW480 and SW620 cells were rather similar in terms of their PL profiles, as suggested by PCA. However, specific PL profiles, as well as accumulation of some PL species (in particular PS, PI and PE) have been proposed to be linked with metastatic potential and aggressiveness of tumor cells in other cancer types, including breast cancer or melanomas, or to increase directly in metastatic cells [44,[48][49][50][51]. This would suggest that, in addition to general alterations of lipid metabolism, PL can be expected to increase also in colon cancer metastases.…”
Section: Mw T/n Ratio Mean (95% Ci) P-valuementioning
confidence: 99%